PENGEMBANGAN COMMUNITY BASED TOURISM (CBT) DI DESA WISATA BISSOLORO KABUPATEN GOWA - Nurhalisa, Nurhalisa; Hakim, Lukman; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to determine the development of CBT in Bissoloro Tourism Village, Gowa Regency and to determine whether there is an influence on visitor interest. The research approach used is descriptive verification. By using data collection techniques through questions given to visitors in the form of questionnaires, also through CBT development documentation. Based on the results of research related to the development of CBT on visitor interest, the following results are obtained: Optimization of CBT-based tourism in the Bissoloro tourist area is included in the quite optimal category. Where each variable assessed is the economic, social, cultural, political and environmental aspects and the highest aspect is the environment. The visitor interest variable is included in the quite optimal category. Where each variable assessed includes attractions, comfort, facilities, infrastructure and accommodation and the highest aspect is accommodation.